If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 19 Solving 5 + -1x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 19 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 19 + -5 -1x = 19 + -5 Combine like terms: 19 + -5 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| (6+w)(2w-9)=0 | | Log[5](x+3)-log[5](x)=1 | | ydx-4xdy=y^6(dy) | | x^2+18x+c= | | 7a+6=15 | | L^2-45l=9000 | | ydx-4xdy=y^6 | | -(2x-3)(5x+4)= | | 3t+5x=10 | | (-2x+3)(5x+4)= | | ydx+(x+y^2)dx=0 | | -[3x-(2x+2)]=-7-[3(2x-4)-3x] | | -(2x+3)(5x+4)= | | 2f-1=13 | | 1-x*y=3 | | 3(2x+3)(7x+5)= | | 3(2x-3)(7x-5)= | | (0.5)(x/0.2)=2 | | (0.5)(x/0.2) | | 2-1*x=3 | | 6(2x+6)=12x | | (21x+4)(x+6)= | | (j-2)3=6j+8 | | 9x-(3x-7)=43 | | (7x-6)(3x-4)= | | 3k=9.75 | | x^3+3*x^2+4x+6=0 | | 2-10*x=0 | | 5=8/y-3 | | 4/3x-3(x-1)=4(x-1)=8 | | 0.33*15+x=x | | -28+7x=9x+32 |